Learners’ Autonomy in Out-Of-Class English Writing Learning Activity of the Third Semester Students of English Education Study Program of Universitas Bandar Lampung - Anggia, Helta; Nahdaleni, Ida (Universitas Islam Negeri Raden Intan Lampung, 2017)
This research were conducted to identify and describe the condition of learners’ autonomy in out-of-class English writing learning activities of the third semester students of English Education Study Program of Universitas Bandar Lampung. Mixed method was used to conduct this research. I used both quantitative and qualitative approach, in form of questionnaire with five points Likert-scale and unstructured interview in collecting the data. The results of this research implied that the students were in medium level of autonomy measured by calculating the overall mean average of the questionnaire (mean=3.20). From the interview, I got that the students were lack of awareness of their writing learning outside the class.